Kajian Motif Wastra Cakra Manggilingan Omah Petrok Troso Dalam Desain Komunikasi Visual - Roffi Siana; Eko Darmawanto; Tristan Alfian (SULUH: Jurnal Seni Desain Budaya, 2022)
Wastra motif is a visual form that is contained in cloth media in its entirety and is formed from stylized plants, animals, and other natural objects. Wastra Cakra manggilingan is one of the Wastra in Jepara which has a message in it. Many people do not know the message contained in Wastra weaving in Troso Village. Visual Communication Design is the science of understanding a message in the form of visuals or images. However, to reveal the message contained in the Wastra Cakra manggilingan motif, the researcher uses a qualitative descriptive method with a semiotic theory approach belonging to Charles Morris. The visual form data of the Wastra Cakra manggilingan motif series were obtained based on oral interviews, and other bibliography. Then an analysis was carried out using semiotics which produced data in the form of a series of descriptive sentences. The results of the study resulted in the form of signs, meanings, and messages contained in the entire Wastra Cakra manggillingan motif. This wastra becomes authentic by using a stylized form that is adapted to the life of the Jepara people in general.